2019
DOI: 10.1091/mbc.e19-09-0500
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions between the DBL-1/BMP-like pathway anddpybody size–associated genes inCaenorhabditis elegans

Abstract: How BMP signaling and other body size regulators interact is not clear. We found interactions between Caenorhabditis elegans DBL-1/BMP and ECM, proteins that may modify or secrete DBL-1, and the SET domain protein BLMP-1. DBL-1 signaling may control downstream targets, some through BLMP-1, that affect size either directly or by feeding back on DBL-1 signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 75 publications
(103 reference statements)
3
18
0
Order By: Relevance
“…In three independent trials, the dbl-1(-); spp-9p::gfp animals when fed on standard lab food, E. coli strain OP50, showed a significantly increased fluorescence, consistent with previous reports (Fig. 4a, e) [21,30]. We observed that animals lacking dbl-1 when fed on S. epidermidis, E. cloacae, and S. marcescens showed a further increase in fluorescence in comparison to the control (dbl-1(-); spp-9p::gfp animals fed on E. coli OP50) ( Fig.…”
Section: Dbl-1 Regulates Endogenous Spp-9 Expression Levelssupporting
confidence: 91%
See 4 more Smart Citations
“…In three independent trials, the dbl-1(-); spp-9p::gfp animals when fed on standard lab food, E. coli strain OP50, showed a significantly increased fluorescence, consistent with previous reports (Fig. 4a, e) [21,30]. We observed that animals lacking dbl-1 when fed on S. epidermidis, E. cloacae, and S. marcescens showed a further increase in fluorescence in comparison to the control (dbl-1(-); spp-9p::gfp animals fed on E. coli OP50) ( Fig.…”
Section: Dbl-1 Regulates Endogenous Spp-9 Expression Levelssupporting
confidence: 91%
“…S2b). These qRT-PCR results support previously reported microarray results and the use of spp-9p::GFP as a reporter for DBL-1 pathway signaling [21,30]. spp-9 expression depends on DBL-1 and other innate immune response signaling pathways, depending on pathogen DBL-1 signaling pathway regulates expression of many innate immunity genes and is also involved in mounting protective immune responses against pathogens [13,18,[44][45][46][47][48].…”
Section: Dbl-1 Regulates Endogenous Spp-9 Expression Levelssupporting
confidence: 89%
See 3 more Smart Citations